2021
DOI: 10.1007/s12630-021-02113-z
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation for patients undergoing cardiac surgery: a systematic review and meta-analysis of randomized controlled trials

Abstract: Iron supplementation has been evaluated in several randomized controlled trials (RCTs) for its potential to increase baseline hemoglobin and decrease red blood cell transfusion during cardiac surgery. This study's main objective was to evaluate the current evidence for iron administration in cardiac surgery patients. Methods We searched MEDLINE, EMBASE, CENTRAL, Web of Science databases, and Google Scholar from inception to 19 November 2020 for RCTs evaluating perioperative iron administration in adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Seven recently published systematic reviews with metaanalyses of RCTs answered a similar PICO question and confirmed our conclusions regarding no effect of preoperative iron monotherapy [25][26][27][28] or a reduced effect of ESAs in addition to oral/IV iron supplementation on blood transfusion rate. [29][30][31] On the contrary, one review found that IV iron supplementation is associated with a significant decrease in blood transfusion rate in both anemic and nonanemic patients undergoing major elective surgery.…”
Section: Comparison With Other Recent Systematic Reviews and Meta-ana...supporting
confidence: 82%
“…Seven recently published systematic reviews with metaanalyses of RCTs answered a similar PICO question and confirmed our conclusions regarding no effect of preoperative iron monotherapy [25][26][27][28] or a reduced effect of ESAs in addition to oral/IV iron supplementation on blood transfusion rate. [29][30][31] On the contrary, one review found that IV iron supplementation is associated with a significant decrease in blood transfusion rate in both anemic and nonanemic patients undergoing major elective surgery.…”
Section: Comparison With Other Recent Systematic Reviews and Meta-ana...supporting
confidence: 82%
“…Because more than half of anemic patients undergoing cardiac surgery have iron deficiency, IV iron therapy preoperatively is recommended [ 2 , 28 , 29 ]. However, the evidence regarding the effect of IV iron on reducing the transfusion rate for cardiac surgery patients with preoperative anemia is limited and unclear [ 2 , 13 , 14 , 30 ].This systematic review and meta-analysis suggested that IV iron did not decrease transfusion rates compared with the control group, which was not consistent with Gupta et al [ 13 ] or Elhenawy et al [ 31 ] as they found a significant association of IV iron treatment with a reduced transfusion rate in cardiac surgery patients (RR 0.81, 95% CI 0.70–0.94, P = 0.005) or other major surgery patients (RR 0.84, 95% CI 0.70 to 0.99, P = 0.04). However, their meta-analysis [ 13 , 31 ] included studies exploring the efficacy of IV iron in nonanemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, future studies with a sufficiently large sample size are needed to focus on patients undergoing cardiac surgery. Further data are also required to examine the role of IV iron in three aspects: [ 1 ] applying IV iron with or without other agents (mainly EPO); [ 2 ] dosage of IV iron; and [ 3 ] time of IV iron administration preoperatively [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies exploring IV iron supplementation prior to cardiac surgery have typically focused on a transfusion-sparing effect [14][15][16]. Systematic reviews published in 2015 [17] and 2022 [18] have concluded that perioperative administration of IV iron in this setting is of uncertain benefit, whilst a recent observational study reported that IV iron therapy increased hemoglobin but had no effect on postoperative outcomes [19].…”
Section: Introductionmentioning
confidence: 99%